A molecular dynamics approach for modeling the geographical distribution of ship collision risk. (1st December 2020) - Liu, Zihao; Wu, Zhaolin; Zheng, Zhongyi
Abstract: Collision is one of the major accidents that put the safety of navigation at risk all the time. The effective monitoring on the geographical distribution of collision risk is conducive to reducing the chance of collision accidents. In this paper, a novel model intended for identifying the geographical distribution of collision risk in water area was proposed on the basis of radial distribution function in molecular dynamics. In this model, ship traffic and ships were converted into a molecular system. After being obtained using an analytical method, collision risk was generalized as distance to model the collision risk by radial distribution function. Finally, a space interpolation technique was applied to visualize the geographical distribution of collision risk. To validate the proposed model, the AIS data contained in Bohai Strait was used to conduct experiment. According to the experimental results, the map as obtained by the proposed model is capable to identify the geographical distribution of collision risk, and is advantageous over the traditional method in the instantaneity and accuracy of identification. Moreover, the proposed model can assist surveillance operators in the monitoring of collision risk and the improvement of work efficiency, thus enhancing the navigational safety in the water area. Highlights: A novel collision risk model based on radial distribution function is proposed. The proposed model can depict the geographical distribution of collision risk in real time. Ship traffic and ships are converted to molecule and atoms. AIS data of Bohai Strait was used to validate the effectiveness of the proposed model. The proposed model can provide surveillance operators with assist in their monitoring work.